Efeitos farmacológicos e possíveis mecanismos de ação da hecogenina em modelos animais de lesão gástricas - Cerqueira, Gilberto Santos (2012)
This study investigates the gastroprotective effects of hecogenin, a steroid saponin isolated from Agave sisalana, on experimental models of gastric ulcer. Male Swiss mice were used in the models of ethanol- and indometacin-induced gastriculcer. To clarify the hecogenin mechanism of action, the roles of nitric oxide (NO), sulfhydryls (GSH), K+ATP channels and prostaglandins were also investigated, and measurements of lipid peroxidation (TBARS assay) and nitrite levels in the stomach of hecogenin-treated and untreated animals were performed. Furthermore, the effects of hecogenin on myeloperoxidase (MPO) release from human neutrophils were assessed in vitro. Our results showed that hecogenin (3.1, 7.5, 15, 30, 60 and 90 mg/kg, p.o.) acutely administered, before ethanol or indomethacin, exhibited a potent gastroprotective effect. Although the pretreatments with L-NAME, an iNOS inhibitor, and capsazepine, a TRPV1 receptor agonist, were not able to reverse the hecogenineffect, this was reversed by glibenclamide, a K+ATP blocker, and indomethacin in the model of ethanol-induced gastric lesions. The hecogenin pretreatment normalized GSH levels and significantly reduced lipid peroxidation and nitrite levels in the stomach, as evaluated by the ethanol-induced gastric lesion model. The drug alone increased COX-2 expression and this effect was further enhanced in the presence of ethanol. It also decreased MPO release and significantly protected the gastric mucosa. In conclusion, we showed that hecogenin presents a significant gastroprotective effect that seems to be mediated by K+ATP channels opening and the COX-2/PG pathway. In addition, its antioxidant and anti-inflammatory properties may play a role in the gastroprotective drug effect.